PROBLEMS OF PHYSICAL AND HEALTH WORK IN THE SCHOOL EDUCATION SYSTEM (Conferencea, 2023)
The article discusses the results of sociological research of subject teachers on the organization of physical culture and health-improving work of the teaching staff in the system of public education